The White album's revolutions: avant-gardism, New Left and pop music - Fenerick, Jose Adriano [UNESP]; Marquioni, Carlos Eduardo (Univ Federal Uberlandia, 2015)
The Beatles' White Album can be seen, simultaneously and paradoxically, as a movement forward and a denial of their previous work (Sgt. Pepper's Lonely Hearts Club Band). In this paper, the White Album is analyzed as the materialization of feeling structure, that was being reconfigured, as far as both the aesthetic economy it brought - from its cover to the songs recorded (making its reading easier due to an approachable repertory) - and the duality in the Revolution (1 and 9) registers are concerned. While the first song suggests musical moderation and political lack of definition, the second one includes differentiated aesthetic experiments in lyrics and music, even in comparison with other experimental Beatles recorded songs. According to this analytic perspective, we could say that Revolution 9 is close to European vanguards and, at the same time, has pop music elements.
Keywords: keywords: Beatles; White album; rock